The Effect of Capital Intensity, Firm Size and Leverage on Tax Avoidance - Hapsari, Pramesti Hajar Budi (Tax Accounting Applied Journal, 2025)
Tax avoidance is a legal strategy to reduce tax payments in accordance with tax laws. Companies use it to minimize tax burdens that could harm their financial performance. This study analyzes the effect of capital intensity, firm size, and leverage on tax avoidance. The sample includes 36 food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2020 to 2024, selected using purposive sampling. Using multiple regression analysis via SPSS 25, the results show that capital intensity and firm size do not significantly affect tax avoidance, while leverage has a significant positive effect on tax avoidance.